Characteristics and impact of exercise-induced laryngeal obstruction: an international perspective. Issue 2 (28th June 2021) - Walsted, Emil S.; Famokunwa, Bamidele; Andersen, Louise; Rubak, Sune L.; Buchvald, Frederik; Pedersen, Lars; Dodd, James; Backer, Vibeke; Nielsen, Kim G.; Getzin, Andrew; Hull, James H.
Background: Exercise-induced laryngeal obstruction (EILO) is a common cause of exertional breathlessness and wheeze yet is frequently misdiagnosed as asthma. Insight regarding the demographic characteristics, laryngeal abnormalities and impact of EILO is currently limited, with data only available from individual centre reports. The aim of this work was to provide a broader perspective from a collaboration between multiple international expert centres. Methods: Five geographically distinct clinical paediatric and adult centres (3 Denmark, 1 UK, 1 USA) with an expertise in assessing unexplained exertional breathlessness completed database entry of key characteristic features for all cases referred with suspected EILO over a 5-year period. All included cases completed clinical asthma workup and continuous laryngoscopy during exercise (CLE) testing for EILO. Results: Data were available for 1007 individuals (n=713 female (71%)) with a median (range) age of 24 (8–76) years, and of these 586 (58%) were diagnosed with EILO. In all centres, EILO was frequently misdiagnosed as asthma; on average there was a 2-year delay to diagnosis of EILO, and current asthma medication was discontinued in 20%. Collapse at the supraglottic level was seen in 60%, whereas vocal cord dysfunction (VCD) was only detected/visualised in 18%. Nearly half (45%) of individuals with EILO were active participants in recreational-level sports, suggesting that EILO is not simply confined to competitive/elite athletes. Conclusion: Our findings indicate that key clinical characteristics and the impact of EILO/VCD are similar in globally distinct regions, facilitating improved awareness of this condition to enhance recognition and avoid erroneous asthma treatment. Exercise-induced laryngeal obstruction is a prevalent cause of exertional breathlessness and wheeze. In this international multicentre collaboration, 1007 patients waited, on average, 2 years for diagnosis and 20% were mistreated as asthmatic. https://bit.ly/3auXpcp